Enteropathy associated T cell lymphoma-monomorphic variant, presenting as bilateral ovarian masses - Priya M. Jacob; Rekha A. Nair; Jay Mehta; Anita M. Borges; S. Suchetha (Wolters Kluwer Medknow Publications, 2014)
Enteropathy associated T cell lymphoma (EATL) is a rare type of T-cell lymphoma, often associated with a history of celiac disease. It usually arises in the jejunum, but can involve other gastrointestinal tract sites such as stomach and colon. Monomorphic variant of EATL often occurs without a history of celiac disease, has variable histologic evidence of enteropathy, and is usually CD56 + . We report a case of EATL in a 49-year-old female presenting as bilateral ovarian masses. The morphology and immunophenotypic features were compatible with monomorphic variant of EATL.